Acanthocephalans of marine and freshwater fishes from Taiwan with description of a new species - Lisitsyna, Olga; Barcak, Daniel; Orosova, Martina; Fan, Chia-Kwung; Oros, Mikulas (Folia parasitologica, 2023)
During an ichthyoparasitological survey in 2017-2019, six species of acanthocephalans were found among Taiwan's freshwater (Cypriniformes: Xenocyprididae, Cyprinidae) and marine fishes (Scombriformes: Scombridae, Trichiuridae; Anabantiformes: Channidae; Carangaria/misc: Latidae): Micracanthorhynchina dakusuiensis (Harada, 1938), Rhadinorhynchus laterospinosus Amin, Heckmann et Ha, 2011, Pallisentis rexus Wongkham et Whitfield, 1999, Longicollum sp., Bolbosoma vasculosum (Rudolphi, 1819), and one new species, Micracanthorynchina brevelemniscus sp. n. All species are morphologically characterised and illustrated using light and scanning electron microscopy. The finding of R. laterospinosus, P. rexus and B. vasculosum is the first record for these species in Taiwan. Micracanthorhynchina brevelemniscus is similar to Micracanthorhynchina motomurai (Harada, 1935) and M. dakusuiensis in proboscis armature but differs from M. motomurai by larger eggs (53-59 × 15-16 µm vs 40 × 16 µm) and by the number of cement glands (6 vs 4) and from M. dakusuiensis by shorter body length (2.2-2.9 mm vs 4.0 mm in males and 2.9-4.1 mm vs 7.6 mm in females), by the location of the organs of the male reproductive system (from level of the posterior third of the proboscis receptacle in M. brevelemniscus vs in the posterior half of the trunk in M. dakusuiensis), and by length of lemnisci (lemnisci shorter than the proboscis receptacle vs lemnisci longer than the proboscis receptacle). Phylogenetic analyses of almost complete 18S rRNA gene revealed paraphyly of the family Rhadinorhynchidae suggested in previous studies. Micracanthorhynchina dakusuiensis and M. brevelemniscus formed a strongly supported cluster, which formed the earliest diverging branch to the rest of the rhadinorhynchids and transvenids.
Keywords: taxonomy; nemoci ryb; Helminthiasis, Animal; Phylogeny; Fish Diseases; ryby; helmintózy zvířat; host specificity; Female; zvířata; comparative morphology; Acanthocephala; máloostní; Cypriniformes; Fishes; ženské pohlaví; Male; fylogeneze; Animals; molecular phylogeny; mužské pohlaví; Taiwan; Perciformes